Persistence and antibiotic immunity of bacteria from a wetland used as a medical waste landfill. - Boening DW; Vasconcelos GJ (Journal of Environmental Health)
The rudimentary objective of any biomedical waste disposal program should be protection of both public health and the environment. From 1964 to 1978, a wetland located in western Washington State was used as a landfill for non-sterilized medical wastes from Seattle area hospitals. Previous investigations classified the site as a threat to harvestable fish and shellfish inhabiting areas adjacent to the wetland. Slough waters, sediments, and leachate samples revealed high levels of total and fecal coliforms, fecal streptococci, and the opportunistic pathogens Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis, and the anaerobe Clostridium perfringens. Site investigations have included susceptibility testing to identify pathogen resistance to antibiotic and chemotherapeutic agents commonly use in Seattle area hospitals during the period of landfill operations, Although significant decreases in both indicator and pathogen populations has occurred since 1974, the prolonged rate of decrease is rather atypical of a landfill milieu. The persistence of even small populations of drug-resistant, opportunistic pathogens can make the treatment of environmentally-acquired infections much more difficult.